Analysis of Personal Protective Equipments Pesticides Usage Effects on Health Complaints of Farmers in Pringgondani Village Sumberjambe District Jember Regency - BJ Azmy As'ady; Supangat Supangat; Laksmi Indreswari (Journal of Agromedicine and Medical Sciences, 2019)
Jember is one of the districts in East Java Province with the majority of its population working as farmers. Pringgondani Village Farmers in Jember use pesticides when farming. Pesticides contain harmful chemicals. Use of PPE (Personal Protective Equipments) can protect farmers when mixing and spraying pesticides. This study aims to analyze correlation between PPE pesticides usage and health complaints of farmers in Pringgondani Village Sumberjambe District Jember Regency. Cross sectional surveys were conducted on 50 samples. Data were collected by interview using questionnaire. Data were analyzed by chi square test to know correlation between PPE pesticides use (protective clothing, head protection, mask, gloves and boots) and health complaints (headache, increased fatigue, itching and nausea). Chi square test result showed significance 0,043 (p <0,05) where there was a correlation between head protector use and health complaint of respondent with contingency coefficient (r) equal to 0,318. The conclusion is that there is a correlation between the head protection use and health complaints of farmers in Pringgondani Village Sumberjambe District Jember Regency with sufficient correlation. Keywords: PPE, pesticides, health complaints, Farmers, Pringgondani, Jember